Influence of cultivation substrate on antioxidant activities and triterpenoid profiles of the fruiting body of Ganoderma lucidum - Luo, Gelian; Pan, Zhibin; Liu, Zhibin; Cheng, Weiqing; Yu, Tingting (Frontiers in Nutrition, 2024)
The fruiting body of Ganoderma lucidum has been believed to possess a wide range of therapeutic effects. There are two main methods for artificial cultivation of G. lucidum to produce the fruiting body, namely wood log cultivation and substitute cultivation. The impact of cultivation substrates on the composition of bioactive compounds remains largely unexplored. This study aims to compare the antioxidant activities and triterpenoid profiles of the fruiting bodies of G. lucidum that cultivated through wood log cultivation (WGL) and substitute cultivation (SGL) methods. The results indicate that WGL samples exhibited significantly higher total triterpenoid content, DPPH radical scavenging activity, and total antioxidant activity. Furthermore, an untargeted metabolomics approach employing UHPLC-Q-Orbitrap-MS tentatively identified a total of 96 triterpenoids. Distinguishingly different triterpenoid profiles between the two types of G. lucidum samples were revealed via the utilization of principal component analysis (PCA) and hierarchical cluster analysis (HCA). Specifically, 17 triterpenoids showed significant differences. Of these triterpenoids, 6 compounds, such as ganosporelactone B, ganoderol A, ganoderic acid A, ganoderic acid alpha, were significantly higher in SGL samples; 11 compounds, such as lucidenic acid A, lucidenic acid D1, lucidenic acid F, lucidenic acid G, lucidenic acid J, ganoderic acid E, and ganoderic acid O, were significantly higher in WGL samples. These findings expand our knowledge regarding the impact of cultivation substrate on the antioxidant activities and triterpenoid profiles of G. lucidum, and offer practical implications for its cultivation.